Who will Bear the Brunt of Lockdown Policies? : Evidence from Tele-workability Measures Across Countries - Brussevich, Mariya (IMF Working Papers; Working Paper ;, 2020)
Lockdowns imposed around the world to contain the spread of the COVID-19 pandemic are having a differential impact on economic activity and jobs. This paper presents a new index of the feasibility to work from home to investigate what types of jobs are most at risk. We estimate that over 97.3 million workers, equivalent to about 15 percent of the workforce, are at high risk of layoffs and furlough across the 35 advanced and emerging countries in our sample. Workers least likely to work remotely tend to be young, without a college education, working for non-standard contracts, employed in smaller firms, and those at the bottom of the earnings distribution, suggesting that the pandemic could exacerbate inequality. Crosscountry heterogeneity in the ability to work remotely reflects differential access to and use of technology, sectoral mix, and labor market selection. Policies should account for demographic and distributional considerations both during the crisis and in its aftermath.